Eliciting tomato plant defenses by exposure to herbivore induced plant volatiles - Pérez-Hedo, Mertixell; Alonso-Valiente, Miquel; Vacas, Sandra; Gallego, Carolina; Rambla, José L.; Navarro-Llopis, Vicente; Granell, Antonio; Urbaneja, Alberto (Schweizerbart Science Publishers, 2021)
When zoophytophagous mirids (Hemiptera: Miridae) feed on tomato plants they activate both direct and indirect defense mechanisms, which include the release of herbivore induced plant volatiles (HIPVs). HIPVs are capable of activating defense mechanisms in healthy neighboring plants. In this work, we investigated which of these mirid-induced HIPVs are responsible for inducing plant defenses. Healthy tomato plants were individually exposed to eight HIPVs [1-hexanol, (Z)-3-hexenol, (Z)-3-hexenyl acetate, (Z)-3-hexenyl propanoate, (Z)-3-hexenyl butanoate, hexyl butanoate, methyl jasmonate and methyl salicylate] for 24 hours. Then, the expression level of defensive genes was quantified. All HIPVs led to increased expression of defensive genes by the plant when compared to unexposed tomato plants. In a further step, (Z)-3-hexenyl propanoate and methyl salicylate were selected to study the response of four tomato key pests and one natural enemy to tomato plants previously exposed to both HIPVs relative to unexposed control plants. Plants previously exposed to both HIPVs were repellent to Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) and Frankliniella occidentalis Pergande (Thysanoptera: Thripidae), attractive to the parasitoid Encarsia formosa Gahan (Hymenoptera: Aphelinidae) and indifferent to Tetranychus urticae Koch (Acari: Tetranychidae). The volatiles emitted by plants previously exposed to both selected volatiles were also determined. Increased levels of C5 and C6 fatty acid-derived volatile compounds and β-ionone were detected, confirming that both HIPVs significantly activated the lipoxygenase pathway. These results are the starting point to advance the use of volatile compounds as defense elicitors in tomato crops.